Impacts of zero valent iron, natural zeolite and Dnase on the fate of antibiotic resistance genes during thermophilic and mesophilic anaerobic digestion of swine manure. (June 2018) - Zhang, Junya; Sui, Qianwen; Zhong, Hui; Meng, Xiaoshan; Wang, Ziyue; Wang, Yawei; Wei, Yuansong
Highlights: Anaerobic digestion of swine manure could reduce most of ARG except sulII and tetM . Thermophilic digestion was more effective than mesophilic digestion. Zero valent iron and natural zeolite addition could further enhance ARGs reduction. Co-occurrence of MRGs contributed 86.5%–89.9% of ARGs variation among treatments. Abstract: This study investigated the fate of antibiotic resistance genes (ARGs) during mesophilic (mAD) and thermophilic digestion (tAD) of swine manure through zero valent iron (ZVI), natural zeolite and Dnase addition. Changes of microbial community, intI1, heavy metal resistance genes (MRGs) and virulence factors (VFs) were followed to clarify the influencing factors to ARGs reduction. Results showed that AD could realize ARGs reduction with tAD superior to mAD, and ZVI and natural zeolite could further enhance the reduction, especially for natural zeolite addition at mAD. The reduction efficiency of the relative abundance of ARGs was increased by 33.3% and 138.5% after ZVI and natural zeolite addition, respectively, but Dnase deteriorated ARGs reduction at mAD. Most of ARGs could be reduced effectively except sulII and tetM . Network analysis and partial redundancy analysis indicated that co-occurrence of MRGs followed by microbial community contributed the most to the variation of ARGs fate among treatments.